The Effects of Brand Image, Review Beauty Vlogger, and Product Quality on Purchase Decisions for Wardah Cosmetics - Novi Saputri; Khoirul Hikmah (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study is aimed at analyzing the effect of Brand Image , Review Vlogger, and Product Quality on Purchase Decisions for Wardah Cosmetics at Female Management Study Program Students of UPN "Veteran" Yogyakarta. the the research method used in this research is the quantitative method. The population in this study were management students at UPN "Veteran" Yogyakarta . Method of collecting data by using online questioner. The sampling method used was purposive sampling. The analytical tools used are descriptive and quantitative methods using multiple linear regression analysis with the help of the SPSS program version 26. This research finds that (1) there is an influence of brand image, beauty vlogger reviews and product quality on purchase decisions (2) there is no effect of brand image on purchase decisions (3) there is an effect of beauty vlogger reviews on purchase decision (4) there is an effect of product quality on purchase decision.